Ces parfums qui fascinent: mémoires, réminiscences et souvenirs d’un Maghreb perdu chez Claude Brami - Bevilacqua, Elisabetta (Ponti/Ponts, 2021)
Pied-noir and Judeo-Maghrebian Literatures are the expression of themes such as memory, exile, identity. Their authors write in order to save their history – the History of Maghreb before Independences – and transmit their memories to the new generations. In their literary production, a collective memory and an individual memory meet each other and produce a “memorial novel”, as defined by Régine Robin. This paper aims to study Claude Brami’s novel, Parfums des étés perdus (published in 1990 by Gallimard) in relation to this concept, with a particular attention to the role of scents and smells which represent the first manifestation of souvenir.